Organ damage in sickle cell disease study (ORDISS): protocol for a longitudinal cohort study based in Ghana - Anie A Kofi; Paintsil Vivian; Ansong Daniel; Owusu-Dabo Ellis; Osei-Akoto Alex; Ohene-Frempong Kwaku....et al (BJM Open, 2023)
This article is published by BJM Open and is also available at http://bmjopen.bmj.com/